Cocktail effects of clothianidin and imidacloprid in zebrafish embryonic development, with high and low concentrations of mixtures - Zee, Seonggeun; Hyun, Moonjung; Sim, Hee-Jung; Kim, Kanghee; Kang, Ju-Chan; Park, Chang-Beom (Frontiers in Toxicology, 2024)
There is growing concern that sprayed neonicotinoid pesticides (neonics) persist in mixed forms in the environmental soil and water systems, and these concerns stem from reports of increase in both the detection frequency and concentration of these pollutants. To confirm the toxic effects of neonics, we conducted toxicity tests on two neonics, clothianidin (CLO) and imidacloprid (IMD), in embryos of zebrafish. Toxicity tests were performed with two different types of mixtures: potential mixture compounds and realistic mixture compounds. Potential mixtures of CLO and IMD exhibited synergistic effects, in a dose-dependent manner, in zebrafish embryonic toxicity. Realistic mixture toxicity tests that are reflecting the toxic effects of mixture in the aquatic environment were conducted with zebrafish embryos. The toxicity of the CLO and IMD mixture at environmentally-relevant concentrations was confirmed by the alteration of the transcriptional levels of target genes, such as cell damage linked to oxidative stress response and thyroid hormone synthesis related to zebrafish embryonic development. Consequently, the findings of this study can be considered a strategy for examining mixture toxicity in the range of detected environmental concentrations. In particular, our results will be useful in explaining the mode of toxic action of chemical mixtures following short-term exposure. Finally, the toxicity information of CLO and IMD mixtures will be applied for the agricultural environment, as a part of chemical regulation guideline for the use and production of pesticides.